Use of Virtual Reality in Public Relations Campaign - Joshua Kayode Okunade; Toyin O. Akintola (Budapest International Research and Critics University, 2025)
Virtual Reality (VR) has emerged as a transformative technology with the potential to revolutionize various industries, including public relations (PR). VR offers immersive experiences that can engage audiences in ways traditional media cannot. As Virtual Reality (VR) emerges as a potential game-changer in public relations (PR) campaigns, it is essential to assess the challenges and opportunities associated with its integration critically. Two theoretical frameworks, the Technology Acceptance Model (TAM) and the Media Richness Theory (MRT), were deployed in the study. The research adopted a survey method using questionnaire to generate data. This study underscores the transformative potential of VR to enhance audience engagement, brand recall, and emotional connections. The findings reveal that younger, educated, and tech-savvy demographics are particularly receptive to VR, validating its appeal to dynamic audiences. While VR demonstrates strong potential in creating immersive and interactive experiences, barriers such as high costs, limited technical expertise, and compatibility challenges hinder its widespread adoption. The findings reveal that younger, educated, and tech-savvy demographics are particularly receptive to VR, validating its appeal to dynamic audiences. While VR demonstrates strong potential in creating immersive and interactive experiences, barriers such as high costs, limited technical expertise, and compatibility challenges hinder its widespread adoption. This study underscores the transformative potential of VR to enhance audience engagement, brand recall, and emotional connections.